2022
DOI: 10.1002/maco.202112935
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al and Fe additions on metal dusting of NiCr alloys

Abstract: Corrosion by metal dusting causes problems in various industries that process carbonaceous gases. Recently, the chromium‐ and aluminum‐rich Ni‐based Alloy 699 XA was introduced as a material with high resistance against metal dusting attacks. In this study, the metal dusting degradation of Alloy 699 XA and model alloys was investigated. In the model alloys, the aluminum, chromium, and iron contents were varied to analyze the role of each element systematically. Alloy 602 CA was included as a reference material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Exposures under the same conditions were previously reported, which compare the metal dusting performance of 602CA and 699 XA in the ground surface condition and thus no additional reference alloy is included in this study. [ 26 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposures under the same conditions were previously reported, which compare the metal dusting performance of 602CA and 699 XA in the ground surface condition and thus no additional reference alloy is included in this study. [ 26 ]…”
Section: Methodsmentioning
confidence: 99%
“…Exposures under the same conditions were previously reported, which compare the metal dusting performance of 602CA and 699 XA in the ground surface condition and thus no additional reference alloy is included in this study. [26] To study the relationship between different cold rolling levels and sensitivity to metal dusting attack, three samples of the 699 XA 25 mm plate were cold rolled to 2%, 10%, and 50% deformation, as shown in Table 2. Sample number 4 was the reference without cold rolling.…”
Section: Alloy and Surface Treatmentsmentioning
confidence: 99%
“…699 XA, also ground to P1200 grit, was not attacked in this gas even after 1507 h. This confirms the better performance of 699 XA in comparison with the attacked samples of 602 CA, 601, and 690, all ground to P1200 grit in Figure 2. Alloy 699 XA was additionally exposed in gas 2, in which samples of 699 XA ground to P500 grit showed formation of a few pits in the first 480 h, [8,17] implying a more aggressive attack in gas 2. In a previous study, [17] it was also shown that the pit initiation may have significantly changed with surface treatment.…”
Section: On-site Aluminizationmentioning
confidence: 99%
“…[5,6] Even when using Ni-based alloys with high alloying contents of between 25 and 31 wt.% Cr and up to 3 wt.% Al in metal dusting conditions, corrosion can occur. [6][7][8] Welds are especially prone to failure, as they have a slightly different composition, microstructure, residual stress, and surface compared to the base plate or tube. In studies of similar weld joints, the following cases have been observed:…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, when stainless steel is exposed to a corrosive environment for a long time, its performance can be significantly reduced. [6,7] Because problems of pickling pollutants, uneven passivation regions, and serious environmental pollution have been discovered in the pickling passivation of stainless steel, this process does not meet the process requirements of green cleaning. [8][9][10][11] Therefore, it is of great practical significance to develop an economical, environmental, and efficient stainless steel passivation technology.…”
Section: Introductionmentioning
confidence: 99%